Marketing and Socioeconomics Aspects of Large Cardamom Production in Tehrathum, Nepal - Bhandari, Nirajan; Bhandari, Thaneshwar (Journal of Nepal Agricultural Research Council, 2018)
A survey was conducted in November 2015 in one of the pocket area of large cardamom production in Teharthum District, eastern Nepal with aim to investigate the status of cardamom enterprises. The parameters used were cardamom production area, type of manure used, drying facilities, technical skills of farmers, market channels and variable cost etc. We purposively selected 30 cardamom producers and stakeholders for interview pre-designed questionnaires. The result showed that average area, production and productivity of large cardamom per household were 0.86 ha, 200 kg and 232 kg.ha-1, respectively, with the average farming experience of 22 years. It was revealed that 13% farmers used farmyard organic manure, the use of 1.5 kg/plant farmyard manure might produce 28.5% higher yield cardamom compared to without using any manure or fertilizers. It was also revealed among the responded only 7% had received improved drying machine from District Agriculture Development Office (DADO) at 50% subsidy, while only 23% of farmers received training and technical services from DADO. The study showed that per hectare average total cost of large cardamom production, selling price and gross revenue were NRs. 2,36,705 ($2255), NRs. 5,50,305 ($5240) and NRs. 3,13,600 ($2985), respectively, with benefit/cost (B/C) ratio of 2 after the completion of gestation period of 4 years. Our survey showed that predominant marketing approach was by direct sell to the traders located at district headquarter. The productivity of large cardamom was influenced by various factors, such as nearly 75.2% of the variation in productivity was explained by the number of active family members, farming period, area, intercultural operations, variable cost and depreciated fixed cost.